Борис Тен у контексті українсько-грузинських літературних взаємин ХХ ст.: до питання про переклад «Тамаріані» Чахрухадзе - Грицик, Л. (Слово і Час, 2023)
У пропонованій статті осмислюється шлях українського перекладача до «Тамаріані»: причини вибору творів для перекладу; мотивація; роль українських неокласиків М. Зерова, М. Рильського, М. Бажана і його уроків перекладу «Витязя в тигровій шкурі» Ш. Руставелі; пошуки «творчої домінанти» «Тамаріані» Чахрухадзе та свого шляху в різноманітті стилістичних і композиційних авторських рішень. Опрацьовані матеріали, пов’язані з роботою Бориса Тена над «Тамаріані», дають підстави вперше розглядати виконаний переклад у контексті українсько-грузинських літературних взаємин ХХ ст.; акцентувати на своєрідності індивідуального творчого проєкту, зокрема й концептуально-методологічних принципів українського перекладу з грузинської. Based on the study of the Central State Archive-Museum of Literature and Art of Ukraine materials, the work traces the way of Ukrainian translator Borys Ten (M. Khomychevskyi) to Georgian literature. In particular, the paper focuses on the work of Chakhrukhadze as a forerunner of the great Rustaveli, the poem’s role in the literature of the Georgian Middle Ages, the motives for making translation, and reception of the work in Ukraine. The library of the Archive-Museum of Literature and Art of Ukraine received a thirty-page manuscript written in pencil with no title page and no name. Having read it, I immediately recognized Chakhrukhadze’s voice, which made me return to the anthology with fragments of Chakhrukhadze’s poem translated by Borys Ten. The contemporary circle of translators used to be rather stable, and they usualy knew each other well. However, Borys Ten did not typically work with Georgian literature, and the numerous pseudonyms that M. Khomychevskyi used after his exile were known mainly to specialists. Despite the peculiarity of a ten-syllable verse, close to the folk samples as much as possible, the translation sounded naturally, without the slightest artificiality. The intrigue was growing since most archival materials concerned the translation of ancient literature and the issues of translation theory and practice, in particular the treatment of hexameter. Even if we consider that due to circumstances, the author had to use pseudonyms at specific periods of his literary activity, Georgian works were not noticed in his translation practice. There emerges a question, the answer to which would explain the path of Borys Ten to Chakhrukhadze and certain pages of his creative life. To reveal the way of the Ukrainian translator to “Tamariani” one must consider his reasons for choosing the field of translation for a career; the role of Ukrainian neo-classics M. Zerov and M. Rylskyi, as well as M. Bazhan and lessons of his translation of “The Knight in the Panther’s Skin” by Rustaveli; the search of the translator’s own way amidst a variety of stylistic and compositional solutions; the development of personal approach to the rendering of original work; the ‘creative dominant’ of “Tamariani” by Chakhrukhadze.